1998
DOI: 10.1046/j.1472-765x.1998.00451.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on permeabilization treatments for in situ determination of phytase of Rhodotorula gracilis

Abstract: Rhodotorula gracilis, a red yeast, was shown to produce phytase and the cultural conditions were standardized for phytase production. Permeabilization treatments using detergents, organic solvents, enzymes and physical methods were performed and compared by measuring the phytase activity of whole cells. None of the permeabilization methods except the freeze‐thaw method enhanced phytase activity. The enzyme activity of a yeast suspension subjected to 15 cycles of freezing and thawing was 77·26 U g−1 cells. Phyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 17 publications
1
22
0
2
Order By: Relevance
“…The washed cells were transferred to 50 ml of the production medium, which contained 10.0 g/l oat, 30.0 g/l glucose, 15.0 g/l ammonium sulfate, and 20.0 g/l NaCl, pH 5.0, and grown by shaking at 170 rpm and 28°C for 3 days. To determine the optimal medium and cultivation conditions for phytase production by the yeast strain, different phytate-containing substances (corn meal, wheat flour, oat meal, soybean meal, pea meal, horsebean meal, and phytic acid), carbon sources (glucose, sucrose, fructose, maltose, and galactose), and nitrogen sources (ammonium sulfate, ammonium citrate, peptone, beef extract, casein, and tryptone) with different concentrations were added to the medium prepared with distilled water or seawater, and the yeast strain was grown at different pH (3)(4)(5)(6)(7)(8)(9) and temperature (15-35°C).…”
Section: Phytase Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…The washed cells were transferred to 50 ml of the production medium, which contained 10.0 g/l oat, 30.0 g/l glucose, 15.0 g/l ammonium sulfate, and 20.0 g/l NaCl, pH 5.0, and grown by shaking at 170 rpm and 28°C for 3 days. To determine the optimal medium and cultivation conditions for phytase production by the yeast strain, different phytate-containing substances (corn meal, wheat flour, oat meal, soybean meal, pea meal, horsebean meal, and phytic acid), carbon sources (glucose, sucrose, fructose, maltose, and galactose), and nitrogen sources (ammonium sulfate, ammonium citrate, peptone, beef extract, casein, and tryptone) with different concentrations were added to the medium prepared with distilled water or seawater, and the yeast strain was grown at different pH (3)(4)(5)(6)(7)(8)(9) and temperature (15-35°C).…”
Section: Phytase Productionmentioning
confidence: 99%
“…At present, all phytase preparations authorized in the EU as feed additives are produced by recombinant strains of filamentous fungi, and the expressed phytase genes are of fungal origin and originate in two cases from the genus Aspergillus [4]. In the last decade, phytate-degrading enzymes of terrestrial yeasts such as Schwanniomyces castellii [1], Schwanniomyces occidentalis [5], Pichia anomala [6], Arxula adeninivorans [7], Hansenula polymorph [8], and Rhodotorula gracilis [9] also have received increasing attention as they can be easily incorporated into feed diets and are rich in nutrients. However, little is known about phytase-producing marine yeasts.…”
mentioning
confidence: 99%
“…Phytate did not show an inducible effect on phytase production (Sano et al, 1999 ). The red yeast R. gracilis produced phytase constitutively, with maximum production being in a medium lacking phytate in 18 h (Bindu et al, 1998 ). A high phytase yield by C. krusei WZ-001 was attained in 48 h at 30°C and pH 7.0.…”
Section: Productionmentioning
confidence: 90%
“…The yeasts have been reported to be a rich genetic resource for heat-resistant phytases; the possibility of using these phytases in industry has not, however, been extensively investigated. Among others, the red yeast Rhodotorula gracilis (Bindu et al, 1998), Arxula adeninivorans (Sano et al, 1999 ), Pichia anomala (Vohra and Satyanarayana, 2001 ) and Candida krusei WZ-001 (Quan et al, 2001 ) have also been shown to produce phytase. Recently, there was a report on phytase-producing marine yeasts, where ten yeasts with high phytase activity were obtained and identified to be closely related to species of Hanseniaspora uvarum , Yarrowia lipolytica , Kadamaea ohmeri , Issatchenkia orientalis , Candida tropicalis and C. carpophila .…”
Section: Saccharomyces Mellismentioning
confidence: 99%
“…Chemical permeabilization was performed on 50 mg of wet cells suspended in 1 mL of 50 mM sodium acetate buffer (pH 5.0) for 2 h at room temperature in the presence of 1% or 10% (v/v) Triton X‐100, 0.1% or 1% (v/v) Tween‐80, 0.1% or 1% (w/v) sodium dodecyl sulfate (SDS), 1% or 10% (w/v) EDTA, 50% (v/v) ethanol or 0.85% (w/v) NaCl as permeabilization agent. Physical permeabilization was achieved by freeze–thawing for up to 20 cycles (Bindu et al , 1998). The cells were washed twice, resuspended in 50 mM sodium acetate buffer, and assayed for phytase activity.…”
Section: Methodsmentioning
confidence: 99%